Inflation Risks Management Practices and Performance of Real Estate Construction Housing Projects in Kenya; A Case of Real Estate Construction Housing Projects in Busia County - Murunga, Ekisa; Rambo, Charles; Mbugua, John (International Journal of Entrepreneurship and Project Management, 2023)
Purpose: This study was about inflation risk management practices, and performance of real estate construction housing projects in Busia County. Methodology: The target population for this study was 1832 respondents and a sample of 328 was drawn from the target population using Yamane (1967) formula . The data for this study was collected using questionnaires, focus group discussions and interview schedules. Data was analyzed using descriptive and inferential statistics. Descriptive statistics involved quantitative data analysis therefore it used measures of central tendencies such as frequency, percentage, and mean standard deviation, composite mean and composite standard deviation, while inferential statistics involved testing of research hypotheses using pearson correlation and regression analysis. Findings: The study found that inflation risk influences performance of real estate construction housing projects in Busia County; implying that using the Likert scale, the respondents agreed that Inflation Risk Influences Performance of real estate construction housing projects in Busia County. The overall correlation coefficient for Inflation Risk Management and Performance of real estate construction housing projects in Busia County was found to be 0.657 with a p-value of 0.000 < Î±=0.05 implying that from the views of participants in the study the results indicated that there was a significant relationship between Inflation Risk Management and Performance of real estate construction housing projects in Busia County; leading to rejection of the null hypothesis and acceptance of the alternative hypothesis. The simple linear regression coefficients as well as the Pearson correlation results indicated that there was significant influence of Inflation risk management on Performance of real estate construction housing projects in Busia County. In conclusion, the small p-values; implied that there was a significant influence of Inflation risk management on Performance of real estate construction housing projects in Busia County. Unique Contribution to Theory, Practice and Policy: The study recommended that there is need to deliver high number of affordable housing units that will be affordable to low income households irrespective of high levels of inflation.